Kashmir A Tragedy of Errors - Singh, Tavleen (Delhi Viking, 1995)
Tavleen Singh gives a close account of Kashmir issue with a journalistic approach. The book gives a nice perspective about how the Indian political system, Govt (mostly Congress) and post-independent rulers looked at Kashmir and some of acts. But I felt that the author has deliberately omitted a...more...
Keywords: Jammu and Kashmir (India) -- Politics and government; Political crimes and offenses -- India -- Jammu and Kashmi; Separatism